Fluvial morphometry of supraglacial river networks on the southwest Greenland Ice Sheet. Issue 4 (3rd July 2016) - Yang, Kang; Smith, Laurence C.; Chu, Vena W.; Pitcher, Lincoln H.; Gleason, Colin J.; Rennermalm, Asa K.; Li, Manchun
Abstract : Extensive, complex supraglacial river networks form on the southwest Greenland ice sheet (GrIS) surface each melt season. These networks are the dominant pathways for surface meltwater transport on this part of the ice sheet, but their fluvial morphometry has received little study. This paper utilizes high-resolution (2 m) WorldView-1/2 images, digital elevation models, and GIS tools to present a detailed morphometric characterization (river number, river length, Strahler stream order, width, depth, bifurcation ratio, braiding index, drainage density, slope, and relief ratio) for 523 GrIS supraglacial river networks. A new algorithm is presented to determine Strahler stream order in supraglacial environments. Results show that (1) Supraglacial river networks are broadly similar to terrestrial landscapes in that they follow Horton's laws (river number, mean river length, and slope versus stream order), widen downstream, and have comparable mean bifurcation ratios (3.7 ± 1.9) and braiding indices; (2) unlike terrestrial systems, supraglacial drainage densities (0.90–4.75 km/km 2 ) have no correlation with elevation relief, but instead display a weakly inverse correlation with ice surface elevation; (3) both well-developed (e.g., fifth-order) and discrete (e.g., first-order) supraglacial river networks form on the ice sheet, with the latter associated with short flow distances upstream of a terminal moulin; (4) mean river flow widths increase substantially, but flow depths only modestly, with increasing stream order. Viewed collectively, the 523 supraglacial river networks studied here display fluvial morphometries both similar and dissimilar to terrestrial systems, with moulin capture an important physical process driving the latter.